2021
DOI: 10.3390/ijerph18041861
|View full text |Cite
|
Sign up to set email alerts
|

Objectively Measured Built Environments and Cardiovascular Diseases in Middle-Aged and Older Korean Adults

Abstract: This study assesses the association between the objectively measured built environment and cardiovascular diseases (CVDs) in 50,741 adults from the Korean Community Health Survey. The CVD outcomes of hypertension, diabetes, dyslipidemia, stroke, and myocardial infarction (MI) or angina were derived from self-reported histories of physician diagnoses. Using ArcGIS software and Korean government databases, this study measured the built environment variables for the 546 administrative areas of Gyeonggi province. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…In the present study, no correlation was observed between the built environment and chronic diseases. The obtained result is contrary to most studies ( 62–64 ). Our findings are consistent with the findings of Maike Schulz et al ( 65 ) in Germany, who investigated the influence of the built environment on risk factors and health behavior.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, no correlation was observed between the built environment and chronic diseases. The obtained result is contrary to most studies ( 62–64 ). Our findings are consistent with the findings of Maike Schulz et al ( 65 ) in Germany, who investigated the influence of the built environment on risk factors and health behavior.…”
Section: Discussioncontrasting
confidence: 99%
“…We followed three main steps to investigate the in uence of urban built environment on cardiovascular diseases. First, we reviewed the existing literature and identi ed the indicators of built environment elements that affect cardiovascular diseases 33,41,42 . We then collected and processed the relevant data for these indicators.…”
Section: Methodsmentioning
confidence: 99%
“…However, the relationship between different environmental elements and cardiovascular diseases is complex and diverse, and requires advanced statistical methods and spatial analysis models to reveal. Previous studies have mainly used methods such as spatial autocorrelation analysis (Moran's I), ordinary least squares (OLS), geographically weighted regression (GWR), multiscale geographically weighted regression (MGWR), and logistic regression model to quantify and evaluate the impact of built environment on cardiovascular diseases 5,32,33 . These methods can provide useful insights, but they cannot capture the in uence size and degree of various environmental elements on cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis found that neighborhood environmental attributes that promote PA were associated with reductions in several CVD risk factors, including hypertension, diabetes, and obesity [ 7 ]. Moreover, the relationship between the availability of PA facilities and CVD was investigated in several studies in developed western countries, many of which were cross-sectional studies on the prevalence of CVD [ 8 , 9 ] or the cardiovascular health score [ 10 12 ]. A few cohort studies investigated the association of PA facilities with the risk of CVD incidence.…”
Section: Introductionmentioning
confidence: 99%